2020
DOI: 10.3390/ijms21062063
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heat Shock Protein 70 in Mouse RPE as an In Vivo Model of Transpupillary Thermal Stimulation

Abstract: The induction of heat shock response in the macula has been proposed as a useful therapeutic strategy for retinal neurodegenerative diseases by promoting proteostasis and enhancing protective chaperone mechanisms. We applied transpupillary 1064 nm long-duration laser heating to the mouse (C57Bl/6J) fundus to examine the heat shock response in vivo. The intensity and spatial distribution of heat shock protein (HSP) 70 expression along with the concomitant probability for damage were measured 24 h after laser ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The emphasis of these studies has been to apply temperature increases in order to activate the HSR yet to prevent cellular damage [ 23 , 24 , 25 ]. Previous studies have demonstrated the induction of HSPs in the RPE cells after transpupillary laser irradiation [ 24 , 25 , 26 , 27 , 28 , 29 ], which could lead to therapeutical effects [ 24 , 25 , 30 , 31 , 32 ]. However, the molecular mechanisms underlying the beneficial effects of HHS in RPE cells have not been fully unraveled yet.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis of these studies has been to apply temperature increases in order to activate the HSR yet to prevent cellular damage [ 23 , 24 , 25 ]. Previous studies have demonstrated the induction of HSPs in the RPE cells after transpupillary laser irradiation [ 24 , 25 , 26 , 27 , 28 , 29 ], which could lead to therapeutical effects [ 24 , 25 , 30 , 31 , 32 ]. However, the molecular mechanisms underlying the beneficial effects of HHS in RPE cells have not been fully unraveled yet.…”
Section: Introductionmentioning
confidence: 99%
“…The laser-induced therapeutic effect and the retinal damage seems to be defined by the delivered thermal dose rather than chosen treatment modality and parameters [39], [44], [45]. Although the main hypothesis is that the treatment effect is induced by the heating of the RPE [3], [23], [24], [40], it is unclear whether limiting the therapeutic effect to the RPE is necessary or even beneficial if safety concerns associated with SLT could be alleviated. The introduced ERG-based temperature control would enable the optimal thermal dose to be delivered reliably without significant risks for adverse events for long pulse laser treatments such as TTT [21], [40].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is uncertainty about the key mechanisms responsible for delivering the therapeutic effect, the ratio between laser power causing increased HSP70 production and the laser power causing cell death in the irradiated site has been most extensively studied. Laser powers between 50 and 80% of the power causing cellular damage have been reported to trigger increased HSP70 production in the RPE and choroid [22]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid fluctuations in oxygen cause a substantial stress to the retina tissue, which can activate apoptotic pathways that lead to retinal cell death 7 . In line with these findings, an expansion of studies suggests that autophagy is involved in retinal diseases and contributes to the progressive visual dysfunction 8,9 …”
Section: Introductionmentioning
confidence: 90%
“… 7 In line with these findings, an expansion of studies suggests that autophagy is involved in retinal diseases and contributes to the progressive visual dysfunction. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%